Tok Takia's Legacy in Ayutthaya, Thailand: Tracing Qadriyyah Circulations through the Bay of Bengal - Joll, Christopher Mark; Aree, Srawut (Studia Islamika, 2022)
This article fills some of the gaps in the secondary literature about the growing Muslim presence in the Siamese capital of Ayutthaya during the mid-sixteenth century. It does so by reconstructing the arrival of Tok Takia, a miracle-working Sufi missionary who arrived from somewhere in the Indian subcontinent. The study begins with a description of the Tok Takia Complex which consists of a mosque that once was a Buddhist temple and a maqam where Tok Takia was buried in 1579 before introducing references to the former in Thai primary sources. Before dealing with details about Qadriyyah presence across the Bay of Bengal, this research reconstructs the geopolitical and commercial developments from the late fifteenth century contributing to the growth of Muslim—and specifically, Kling Muslims—presence in Ayutthaya mentioned in a range of Siamese and Portuguese primary sources. This paper presents reasons for suggesting that Tok Takia’s missionary activism was connected to the Nagore-e-Sharif complex in present-day Tamil Nadu.